EFNS/MDS‐ES recommendations for the diagnosis of Parkinson's disease. Issue 1 (22nd December 2012) - Berardelli, A.; Wenning, G. K.; Antonini, A.; Berg, D.; Bloem, B. R.; Bonifati, V.; Brooks, D.; Burn, D. J.; Colosimo, C.; Fanciulli, A.; Ferreira, J.; Gasser, T.; et al.
<x xml:space="preserve">Abstract</x> Background A Task Force was convened by the EFNS/MDS‐ES Scientist Panel on Parkinson's disease (PD) and other movement disorders to systemically review relevant publications on the diagnosis of PD. Methods Following the EFNS instruction for the preparation of neurological diagnostic guidelines, recommendation levels have been generated for diagnostic criteria and investigations. Results For the clinical diagnosis, we recommend the use of the Queen Square Brain Bank criteria (Level B). Genetic testing for specific mutations is recommended on an individual basis (Level B), taking into account specific features (i.e. family history and age of onset). We recommend olfactory testing to differentiate PD from other parkinsonian disorders including recessive forms (Level A). Screening for pre‐motor PD with olfactory testing requires additional tests due to limited specificity. Drug challenge tests are not recommended for the diagnosis in de novo parkinsonian patients. There is an insufficient evidence to support their role in the differential diagnosis between PD and other parkinsonian syndromes. We recommend an assessment of cognition and a screening for REM sleep behaviour disorder, psychotic manifestations and severe depression in the initial evaluation of suspected PD cases (Level A). Transcranial sonography is recommended for the differentiation of PD from atypical and secondary parkinsonian disorders (Level A), for the early diagnosis of PD and in the detection of subjects at risk for PD (Level A), although the technique is so far not universally used and requires some expertise. Because specificity of TCS for the development of PD is limited, TCS should be used in conjunction with other screening tests. Conventional magnetic resonance imaging and diffusion‐weighted imaging at 1.5 T are recommended as neuroimaging tools that can support a diagnosis of multiple system atrophy (MSA) or progressive supranuclear palsy versus PD on the basis of regional atrophy and signal change as well as diffusivity patterns (Level A). DaTscan SPECT is registered in Europe and the United States for the differential diagnosis between degenerative parkinsonisms and essential tremor (Level A). More specifically, DaTscan is indicated in the presence of significant diagnostic uncertainty such as parkinsonism associated with neuroleptic exposure and atypical tremor manifestations such as isolated unilateral postural tremor. Studies of [123I]MIBG/SPECT cardiac uptake may be used to identify patients with PD versus controls and MSA patients (Level A). All other SPECT imaging studies do not fulfil registration standards and cannot be recommended for routine clinical use. At the moment, no conclusion can be drawn as to diagnostic efficacy of autonomic function tests, neurophysiological tests and positron emission tomography imaging in PD. Conclusions The diagnosis of PD is still largely based on the correct identification of its clinical features. Selected investigations (genetic, olfactory, and neuroimaging studies) have an ancillary role in confirming the diagnosis, and some of them could be possibly used in the near future to identify subjects in a pre‐symptomatic phase of the disease.